2018
DOI: 10.1186/s13705-018-0159-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental consciousness and choice of bulb for lighting in a developing country

Abstract: Background: Most countries in the world especially those in Asia and Africa have been undertaking policies meant to help promote science, technology and innovation towards meeting some provisions of the Sustainable Development Goals. However, there is still a sizable number of households who have not yet fully embraced energy-saving technologies. This study provides highlights on the economic and environmental benefits for investing in energy-saving light bulbs. Methods: Using a survey and a multistage random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
1
5
1
Order By: Relevance
“…The variables TF and TB have the highest correlation coefficient of 0.5596. We argue in line with Amoah et al [34] that the degree of collinearity is not so severe to inflate our estimates.…”
Section: Next the Following Variables Property Rights [Pr] Tax Burden...supporting
confidence: 91%
“…The variables TF and TB have the highest correlation coefficient of 0.5596. We argue in line with Amoah et al [34] that the degree of collinearity is not so severe to inflate our estimates.…”
Section: Next the Following Variables Property Rights [Pr] Tax Burden...supporting
confidence: 91%
“…In effect, both variables may be considered superfluous but are used as relevant controls in the model. This evidence contradicts with the study of Amoah et al (2018), which found local and international knowledge to be relevant in making environmentally friendly choice decisions.…”
Section: Forest Depletion In Ghanacontrasting
confidence: 93%
“…(Takouleu, 2020) are also potential CDM projects. The replacement of 172800 compact fluorescent lamps (CFL) by LED lamps in the framework of the "National CFL exchange program" (Amoah et al, 2018), and the replacement of 8150 inefficient fridges by more efficient ones in the framework of the "Refrigerator rebate and exchange scheme" (Graphic Online, 2016;UNDP, 2015) in Ghana are also unharnessed potential opportunities for the CDM. These are just to name a few of such projects in African countries.…”
Section: Registered Cdm Projects Distribution By Region and By Sectoral Scopementioning
confidence: 99%